Model Kelembagaan Pemerintah Desa - Nia Agustina; Esa Esa; Mohamad Yusuf (Institut Nalanda, 2024)
In Law Number 6 of 2014 concerning Villages, it is stated that villages and traditional villages or what are called by other names are legal community units that have territorial boundaries and are authorized to regulate and manage government affairs, the interests of local communities based on community initiatives, rights of origin, and /or traditional rights recognized and respected in the government system of the Unitary State of the Republic of Indonesia. The Village Head or other designation is a Village Government official who has the authority, duties and obligations to organize the Village household and carry out tasks from the Government and Regional Government. Organizational Structure and Work Procedures Village Government is an institutional system in arranging tasks and functions as well as work relationships. According to Village Law, villages are led by a set of village officials known as the village government. However, what often happens is that village government is often confused or even misunderstood with village government